"Reverse Gradualism", Investment Collapse and Monetary Degradation in Russia in the 1990s - Rozmainsky, I.V. (Економічний вісник Донбасу, 2014)
In the 1990s The Russian transitional economy was characterized by many adverse economic processes, but the very important are two of these ones. The first one was the long and biggest fall in output and fixed capital investment. The second was monetary degradation which is increase of primitive mediums of exchange and means of payment – cash, interenterprise arrears ("non-payments") and barter – and (relative and absolute) decrease of "advanced" kinds of money. The goal of this article is to explain interconnections between these processes. The main idea is that these phenomena were generated by shock therapy policy which is turned to be a something like “reverse gradualism”. It means that shock therapy policy is the immediate introduction of all reforms but is not immediate completion of all ones. If that policy takes place, logically later reforms are ended more early because of its extremely small relative duration! That was a case of Russia in the 1990s. У 1990-і роки російська перехідна економіка характеризувалася безліччю несприятливих економічних процесів, але найважливішими були два з них. Перший - тривалий і величезний спад виробництва і інвестицій в основний капітал. Другий - грошова деградація, що була збільшенням ролі примітивних засобів обміну і засобів платежу - готівки, неплатежів і бартеру - укупі з відносним і абсолютним зменшенням ролі «просунутих» видів грошей. Мета цієї статті полягає в поясненні взаємозв'язків між цими процесами. Основна ідея полягає в тому, що ці феномени генерувалися політикою шокової терапії, яка виявилася чимось на зразок «зворотного градуалізму». Останнє означає, що політика шокової терапії є миттєвим впровадженням усіх реформ, але не їх миттєвим завершенням. Якщо така політика здійснюється, то ті реформи, які логічно мали б бути проведені пізніше, реалізуються раніше із-за їх надзвичайно малої відносної тривалості. Це і відбувалося в Росії в 1990-і роки. В 1990-е годы российская переходная экономика характеризовалась множеством неблагоприятных экономических процессов, но самыми важными были два из них. Первый – длительный и громадный спад производства и инвестиций в основной капитал. Второй – денежная деградация, представлявшая собой увеличение роли примитивных средств обмена и средств платежа – наличности, неплатежей и бартера – вкупе с относительным и абсолютным уменьшением роли «продвинутых» видов денег. Цель этой статьи заключается в объяснении взаимосвязей между этими процессами. Основная идея состоит в том, что эти феномены были генерированы политикой шоковой терапии, которая оказалась чем-то вроде «обратного градуализма». Последнее означает, что политика шоковой терапии является мгновенным внедрением всех реформ, но не их мгновенным завершением. Если такая политика осуществляется, то те реформы, которые логически должны были бы быть проведены позже, реализуются раньше из-за их чрезвычайно малой относительной длительности. Это и происходило в России в 1990-е годы.